2016
DOI: 10.1200/jco.2015.63.1325
|View full text |Cite
|
Sign up to set email alerts
|

Upfront Genotyping of DPYD*2A to Individualize Fluoropyrimidine Therapy: A Safety and Cost Analysis

Abstract: DPYD*2A is strongly associated with fluoropyrimidine-induced severe and life-threatening toxicity. DPYD*2A genotype-guided dosing results in adequate systemic drug exposure and significantly improves safety of fluoropyrimidine therapy for the individual patient. On a population level, upfront genotyping seemed cost saving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
356
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(401 citation statements)
references
References 31 publications
16
356
0
4
Order By: Relevance
“…Deenen et al recently reported on 2,038 patients who were prospectively screened for DPD*2A variant, of whom 22 were found to be heterozygous [80]. The most common tumor type in this study was colorectal cancer, and 90% of patients were treated with the oral fluoropyrimidine capecitabine while the remaining 10% of patients were treated with intravenous 5-FU.…”
Section: Dihydropyrimidine Dehydrogenase (Dpd)mentioning
confidence: 84%
“…Deenen et al recently reported on 2,038 patients who were prospectively screened for DPD*2A variant, of whom 22 were found to be heterozygous [80]. The most common tumor type in this study was colorectal cancer, and 90% of patients were treated with the oral fluoropyrimidine capecitabine while the remaining 10% of patients were treated with intravenous 5-FU.…”
Section: Dihydropyrimidine Dehydrogenase (Dpd)mentioning
confidence: 84%
“…Quellen: [1064,1065] Konsens Hintergrund Die Dihydropyrimidin-Dehydrogenase (DPD) ist das SchlĂŒssel-enzym fĂŒr den 5-FU Metabolismus. DPD inaktiviert etwa 80 -90 % des verabreichten 5-FU zu 5,6-Dihydrofluorouracil.…”
Section: Level Of Evidence 2bunclassified
“…Der Genpolymorphismus des kodierenden DPYD-Gens ist die am besten beschriebene Ursache eines DPD-Mangels. Etwa 3 -5 % der Kaukasier weisen einen partiellen und 0,2 % einen kompletten DPDMangel auf [1064]. Nicht funktionelle Allele sind u. a. die Varianten DPYD*2A und DPYD*13, DPYD*9A sowie die SNP-Variante rs67 376 798. Der DPYD*2A Polymorphismus ist mit einer HĂ€ufigkeit von 1 -2 % in den westlichen Nationen die klinisch relevanteste Variante.…”
Section: Level Of Evidence 2bunclassified
See 1 more Smart Citation
“…3,[9][10][11][12] Importantly, upfront screening for risk-associated DPYD variants and dose adaptation in patients carrying variant alleles has shown to be a feasible strategy to improve the safety of patients who carry DPYD variants. 13 At present, clinical validity has been demonstrated for four DPYD variants: c.1905 1 1G>A (DPYD*2A, IVS14 1 1G>A, rs3918290), c. 2846A>T (rs67376798), c.1679T>G (DPYD*13, rs55886062) and c.1129-5923C>G (rs75017182; in complete linkage with the haplotype HapB3). 14,15 A fifth variant, c.1601G>A (DPYD*4, rs1801158), has also been linked to altered DPD activity and fluoropyrimidine-associated toxicity, but the available evidence on clinical validity is less consistent.…”
mentioning
confidence: 99%